KEANEKARAGAMAN JENIS DAN INTENSITAS SERANGAN RAYAP TANAH DI TIGA TIPE TANAH DI AREAL BEKAS KEBUN KARET - Ginuk Sumami; Agus Ismanto (Jurnal Penelitian Hasil Hutan, 1988)
This  paper  deals   with  a study  on  the  infestation   intensity  of subterranean   termites  on three soil types  in clear felled rubber plantation areas in West Java. The soil types  predominating the  areas are  Red  Podzolic,  Brown Latosol  and Dark Grey  Grumusol. The  results  reveal   that  four  species  of  termite  Microtermes insperatus Kemner,   M. incertoides Holmgren, Macrotennes gilvus   (Hagen)  and  Capritermes buitenzorgi  Holmgren   are found   in these  areas pie  termites   were  mostly found  on  the  Dark  Grey Grumusol   soil,   and  the  least number  of  termite  was found  at the Red Podzolic  soil.The  results  also reveal  that  the  soil  type  gave significant  effect to  the  infestation   intensity  of subterranean   termite, but  it did  not give any effect  to the community  of the termite.